Molecular Profiling of Liver Sinusoidal Endothelial Cells in Comparison to Hepatocytes: Reflection on Which Cell Type Should Be the Target for Gene Therapy - El-Maarri, Osman; Jamil, Muhammad Ahmer; Oldenburg, Johannes (Hämostaseologie, 2020)
Human factor VIII (FVIII), which deficiency leads to hemophilia A, is largely synthesized and secreted by the liver sinusoidal endothelial cells (LSECs). However, the characteristics of these cells that secrete FVIII are not well known. We have previously reported that based on genome-wide expression and CpG methylation profiling, LSECs have a distinct molecular profile that distinguishes them from other endothelial cells. Hepatocytes are targeted by gene therapy protocols to treat hemophilia A. However, the hepatocyte is not the natural site for FVIII synthesis and current gene therapy protocols are eliciting immune responses that require immune suppression with corticosteroid therapy in a fairly high proportion of patients over a significant period of time. Cellular stress because of ectopic FVIII expression and codon optimization are discussed as potential underlying mechanisms. Here, we highlight the molecular differences between LSECs and hepatocytes.
Keywords: hepatocytes; expression profiling; methylation profiling; expression–methylation correlation; endothelial cells; F8 protein; gene therapy